Spontaneous regression of a systemic ALK (+) anaplastic large cell lymphoma carrying ALK gene rearrangement that developed after PPD tuberculin skin test - Beköz, Hüseyin Saffet; Kantarcıoğlu, Bülent; Tecimer, Tülay; Sargın, Deniz (Taylor & Francis Ltd, 2016)
Here we report an ALK ( ) ALCL carrying ALK gene rearrangement that developed after a PPD tuberculin skin test, which spontaneously regressed after an excisional lymph node biopsy and is still in complete remission more than 5 years later without treatment. Written informed consent was obtained from the patient for publication of this manuscript and accompanying images. A man aged 38 years was admitted to our hematology clinic on receipt of his excisional biopsy pathology report in October 2008. Th e patient was otherwise healthy and he was asymptomatic. In August 2008, he had noticed aching and swelling in his left armpit 2 – 3 days after a purifi ed protein derivative (PPD) skin test had been conducted to his left arm.
WOS: 000368511800041
PubMed ID: 26059060
Keywords: Spontaneous; Regression of a Systemic; ALK; Lymphoma Carrying; PPD